ISLAMIC EDUCATION AND THE 21ST CENTURY CHALLENGE; THE URGENCY AND ADOLESCENT LITERACY METHOD FOR SOCIAL MEDIA - Muhammad Zuhaery (Pondok Pesantren Modern Islam Assalaam, 2018)
The growing advances in the communication and information technology that is identified by the presence of social media have made changes in the relationship patterns between humans. Through the social media, people can be visually connected to each other without having to meet physically. Because of this, the exchange of values cannot be avoided. The result is a very fast change and exchange of values. This study is aimed to discuss the urgency of the social media literacy for Muslim youth in preparing the generation of Muslim youth into the global environment in the social media era. This study is a qualitative descriptive study. The data used is library data. The result and discussion are that the Islamic education can be the basic capital to prepare the generation of Islamic youth entering the global environment. The values that are taught in Islam can be a filter for the current generation of Muslims to interact with the new media, one of which is the existence of social media platform.